Using Research to Promote Literacy and Reading in Libraries: Guidelines for Librarians - Muhittin Gürbüz; Güler Demir (Türk Kütüphaneciliği)
While literacy and promoting reading are essential factors in developed societies, they are also one of the most crucial missions of all types of libraries. Research activities carried out by librarians and other related partners enable this process to be completed efficiently. This document is the translation of the latest revision of 2011guidelines issued by IFLA (Lesley Farmer and Ivanka Stricevic) that aims to explore aforementioned issues.